Implementation of learning strategies to develop the reading skill as preparation for a standardized international test of english communication skills - Cárdenas Guevara, Carolina 1991-; García Mesen, Yosimar 1987-; Gradiz Arana, Rafael 1988-; Solano Solano, Cristina; Ugalde Barrantes, Lucía 1991-; Valdelomar Miranda, Netzi 1973- ([San José, Costa Rica], 2017)
This project aims to disco ver whether the implementation of the strategies skimming, scanning, guessing meaningfrom context and identifying parts of speech can help students improve their reading skills when taking a standardized test. The participants of this project were two experimental groups and one control group from a private language institution; each experimental group was trained in the usa ge of two different reading strategies. In order to obtain enough data, the researchers worked with both experimental groups for four sessions. During the first session, the researchers applied a pre-test to assess students' previous knowledge. On the second and third sessions, the strategies were taught in an explicit manner. Finally, during the last session a post-test andan interview were used to contrast the data gathered from the pre-test and to obtain students' opinions respectively. The findings of this research study varied a lot; however, the researchers concluded that even when the implementation ofreading strategies can in fact help students highly improve their reading skills, external factors such as work and students' attitudc towards the study can negatively affect the final results.
Seminario de graduación (licenciatura en la enseñanza del inglés como lengua extrangera)--Universidad de Costa Rica. Escuela Formación Docente. Escuela de Lenguas Modernas, 2017
Keywords: INGLES -- ESTUDIO Y ENSEÑANZA; DESARROLLO DE LA LECTURA